Long-term aging of CVD grown 2D-MoS2 nanosheets in ambient environment - Nitul S. Rajput; Ahmed Kotbi; Khaled Kaja; Mustapha Jouiad (npj Materials Degradation, 2022)
Abstract A chemically vapor deposited MoS2 nanosheets (NSs) is aged in the laboratory at ambient and at 40% average humidity for ~36 months. Nanorods of few microns in length and few nanometers in diameter are found to grow from the MoS2 seeds. They have been growing as a result of the chemical reaction between the MoS2 NSs and ambient O2 and moisture, they exhibit an amorphous phase structure in the stoichiometric form of MoO3. Density functional theory simulations further reveal the role of H2O and O2 in the transformation of the MoS2 NSs. The adsorption energy of O2 molecules on the MoS2 sites is E ad = −1.09 eV as compared to lowest absolute E ad = −0.10 eV of H2O indicating the favorable adsorption of O2 and subsequent Mo oxidation. This study provides valuable insight into the aging phenomenon of MoS2 exposed to O2 and moisture which might limit their application.